Urban Farming Generasi Milenial Karang Taruna Dusun Walang Sukoharjo - Novian Wely Asmoro; Sri Hartati; Agustina Intan Niken Tari; Purwanto Purwanto; Muhammad Fathul Anwar (Universitas Mathla'ul Anwar Banten, 2022)
URBAN FARMING FOR THE MILLENIAL GENERATION OF THE YOUTH ORGANİZATİON, DUSUN WALANG SUKOHARJO. Currently, the motivation and interest of the younger generation in agricultural activities is relatively low, from BPS data, 11% of the younger generation are involved in agricultural activities. The purpose of community service activities is to provide an introduction to urban farming that targets the millennial generation, in this case members of the youth organization, so as to increase the motivation and interest of the millennial generation in the agricultural sector through interesting agricultural activities. The method is carried out through several stages of activity, namely Phase I, counseling and delivering material on the concept of urban farming and managing household waste into liquid fertilizer, compost and organic growing media. Phase II, Submission of Verticulture Concept Materials for Anticipating Narrow and Limited Land in Urban Areas. Phase III, Introduction & Practice of Urban Farming Implementation Evaluation of activities using the pretest, posttest and practice assessment methods. The evaluation results show that 93% of partners are involved in this activity and provide an increase in the understanding of the partner community by 85%, where the value of the initial understanding of partner activities towards urban farming cultivation is 54%, then after the activity the value of understanding is 100%.